Songsas Resistance Language Against Domination: A Case study on" Hikayat perang sabil" in Aceh and" Oh Freedom" in the black American Society - Ulyati Retno Sari (Suka Press UIN Sunan Kalijaga, 2010)
ngdm,2/nr,c.1-2